JURIDICAL ANALYSIS OF AGGRAVATED THEFT BASED ON (DECISION NUMBER 1150/PID.B/2024/PN MDN) - Zeno Eronu Zalukhu; Suci Ramadani; Ismaidar (RADJA PUBLIKA, 2026)
This study aims to conduct a juridical analysis of the application of criminal law in cases of aggravated theft as adjudicated in Decision Number 1150/PID.B/2024/PN MDN (Medan District Court). The primary focus is to identify and examine the conformity between the legal facts revealed during the trial and the elements of theft as stipulated in Article 363 of the Indonesian Criminal Code (KUHP), as well as the legal considerations of the judge in rendering the verdict. The research method employed is normative-empirical with a case study approach. The main data source is Decision Number 1150/PID.B/2024/PN MDN, supported by literature studies related to criminal law theory, aggravated theft, and court decisions. The analysis indicates that the panel of judges carefully considered the fulfillment of the elements of aggravated theft, particularly the existence of at least one aggravating factor (for instance, the act was committed at night or involved two or more individuals). The juridical considerations of the judges in this decision are deemed consistent with the provisions of Article 363 KUHP and the applicable principles of criminal law. This study concludes that the decision reflects a balanced law enforcement approach between legitimate proof and the imposition of fair sanctions. The implication of this research highlights the importance of careful verification of aggravating elements to ensure legal certainty and justice.